Epigenome-Wide Analysis Reveals DNA Methylation Alteration in ZFP57 and Its Target RASGFR2 in a Mexican Population Cohort with Autism - Queletzu Aspra; Brenda Cabrera-Mendoza; Mirna Edith Morales-Marín; Carla Márquez; Carlos Chicalote; Ana Ballesteros; Miriam Aguilar; Xochitl Castro; Amalia Gómez-Cotero; Ana María Balboa-Verduzco; Lilia Albores-Gallo; Omar Nafate-López; et al. (MDPI AG, 2022)
Autism Spectrum Disorders (ASD) comprise a group of heterogeneous and complex neurodevelopmental disorders. Genetic and environmental factors contribute to ASD etiology. DNA methylation is particularly relevant for ASD due to its mediating role in the complex interaction between genotype and environment and has been implicated in ASD pathophysiology. The lack of diversity in DNA methylation studies in ASD individuals is remarkable. Since genetic and environmental factors are likely to vary across populations, the study of underrepresented populations is necessary to understand the molecular alterations involved in ASD and the risk factors underlying these changes. This study explored genome-wide differences in DNA methylation patterns in buccal epithelium cells between Mexican ASD patients (n = 27) and age-matched typically developing (TD: n = 15) children. DNA methylation profiles were evaluated with the Illumina 450k array. We evaluated the interaction between sex and ASD and found a differentially methylated region (DMR) over the 5'UTR region of ZFP57 and one of its targets, RASGRF2. These results match previous findings in brain tissue, which may indicate that ZFP57 could be used as a proxy for DNA methylation in different tissues. This is the first study performed in a Mexican, and subsequently, Latin American, population that evaluates DNA methylation in ASD patients.